Simvastatin inhibits Sonic Hedgehog signaling and stemness features of pancreatic cancer - Yin, Yefeng; Liu, Li; Zhao, Zhefu; Yin, Libo; Bauer, Nathalie; Nwaeburu, Clifford C.; Gladkich, Jury; Gross, Wolfgang; Hackert, Thilo; Sticht, Carsten; Gretz, Norbert; Strobel, Oliver; et al. (Cancer letters, 2018)
Pancreatic ductal adenocarcinoma (PDA) has poor therapeutic options. Recent patient studies indicate that cholesterol-lowering statins have anti-tumor capacities. We examined several established and primary PDA and normal cell lines as well as PDA patient tissues (n=68). We found that simvastatin inhibited viability, stemness, tumor growth and metastasis and that it enhanced the efficacy of gemcitabine. These changes were associated with modulation of Shh-related gene expression. Overexpression of Shh prevented the anti-cancer effect of simvastatin, and inhibition of Shh mimicked the simvastatin effect. In PDA tissues, expression levels of Shh, downstream mediators of Shh and progression markers, namely, cMet, CxCR4 and Vimentin, were lower when patients were prescribed statin medication prior to surgery. These results suggested that statins are cost effective and well-tolerated drugs for prevention and co-treatment of PDA.